Comparison of the use of sodium carbonate (washing soda crystals) and apomorphine for inducing emesis in dogs. Issue 12 (6th November 2016) - Yam, E; Hosgood, G; Smart, L
Abstract : Objective: To describe the use of sodium carbonate and apomorphine in a historical cohort of dogs, compare the occurrence of emesis and report any adverse effects recorded. Methods: This historical, observational study included information from medical records of dogs that received an emetic agent. The occurrence of emesis with apomorphine or sodium carbonate was calculated and the association between emesis and agent was explored, with the odds ratio and 95% confidence interval (CI) reported. A non‐inferiority analysis of the occurrence of emesis for sodium carbonate was performed against an equivalence range of ±7% of the estimated occurrence of emesis with apomorphine. Owners were emailed a short survey about their dog's health after their visit to the hospital for induced emesis. Results: Records for 787 dogs seen from January 2007 to December 2013 were included. For apomorphine, 382/392 dogs showed emesis (97%, 95% CI 95–100%). For sodium carbonate, 320/395 dogs showed emesis (81%, 95% CI 77–85%), which fell below the equivalence range for apomorphine (97 ± 7%, 90–100%) and was considered inferior. The odds ratio of emesis with apomorphine to sodium carbonate was 9.0 (95% CI 4.6–17.6). Of 18 responses to the survey, 5 reported abnormalities after emesis (3 with sodium carbonate, 2 with apomorphine). Conclusion: The occurrence of emesis with sodium carbonate was high but inferior to apomorphine. However, the advantages of sodium carbonate, including less expense and ease of accession compared with apomorphine, make it a viable choice in emergency medicine.